Antileishmanial activity of dimeric flavonoids isolated from arrabidaea brachypoda - Rocha, Vinícius P.C.; Da Rocha, Cláudia Quintino; Queiroz, Emerson Ferreira; Marcourt, Laurence; Vilegas, Wagner [UNESP]; Grimaldi, Gabriela B.; Furrer, Pascal; Allémann, Eric; Wolfender, Jean-Luc; Soares, Milena B.P. (MDPI, 2019)
Leishmaniasis are diseases caused by parasites belonging to Leishmania genus. The treatment with pentavalent antimonials present high toxicity. Secondary line drugs, such as amphotericin B and miltefosine also have a narrow therapeutic index. Therefore, there is an urgent need to develop new drugs to treat leishmaniasis. Here, we present the in vitro anti-leishmanial activity of unusual dimeric flavonoids purified from Arrabidaea brachypoda. Three compounds were tested against Leishmana sp. Compound 2 was the most active against promastigotes. Quantifying the in vitro infected macrophages revealed that compound 2 was also the most active against intracellular amastigotes of L. amazonensis, without displaying host cell toxicity. Drug combinations presented an additive effect, suggesting the absence of interaction between amphotericin B and compound 2. Amastigotes treated with compound 2 demonstrated alterations in the Golgi and accumulation of vesicles inside the flagellar pocket. Compound 2-treated amastigotes presented a high accumulation of cytoplasmic vesicles and a myelin-like structure. When administered in L. amazonensis-infected mice, neither the oral nor the topical treatments were effective against the parasite. Based on the high in vitro activity, dimeric flavonoids can be used as a lead structure for the development of new molecules that could be useful for structure-active studies against Leishmania.
Keywords: Arrabidaea brachypoda; Flavonoids; High content; Leishmania